Pathogens, Testing and Vaccines: California Dentists' Role in the Public Health Response to COVID-19 - Richard Graham; Richard Barnes; Tooka Zokaie; Mary McCune (Taylor & Francis Group, 2023)
ABSTRACTBackground The practice of Dentistry has adapted in the past after encountering transformational episodes with novel pathogens. This article highlights two examples of how dentists in California were granted privileges to expand their scope of practice into areas of diagnostics and prevention while at the same time incorporating new barriers to an airborne pathogen. The SARS-Cov-2 virus elevated the scope of universal precautions in dentistry with changes to acceptable PPE, administrative practices, airspace filtering and the screening of patients - including the use rapid testing for SARS-Cov-2. When a COVID-19 vaccine became available, dentists were approved to be vaccinators for the first time in California. Creation of opportunities to vaccinate at every entry point into the healthcare system, including dental offices, was vital for increased access to preventive care.Practical Implications Dentists can play a major role in disease prevention and continued advocacy for removing barriers to their role in pandemic response should continue. Coordinating with medical partners to provide testing and community vaccine confidence is necessary to help combat future flu seasons and Covid surges. With improvement in the technology of diagnostics, delivery of care, and improving patient outcomes, dental clinicians can effectively integrate disease prevention if system barriers are removed.